2001
DOI: 10.1017/s0031182001008149
|View full text |Cite
|
Sign up to set email alerts
|

Multiple strategies of schistosomes to meet their requirements in the intermediate snail host

Abstract: The results of the studies on our model combination Trichobilharzia ocellata-Lymnaea stagnalis, presented in this review, lead to the conclusion that schistosomes use multiple strategies to reach their goals, i.e. to propagate and to continue their life cycle. They have to escape from being attacked by the internal defence system (IDS) of the snail host and to profoundly affect the host's energy flow, of which reproduction and growth are the main determinants, for their own benefit. These physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 43 publications
1
66
0
Order By: Relevance
“…Both molecules, produced in L. stagnalis by granular cells of connective tissue, are related to phagocytic activity of hemocytes. MDM enhances phagocytosis of hemocytes, and the expression of a corresponding gene for MDM is downregulated in L. stagnalis infected with T. szidati (159,161). In contrast, treatment of hemocytes with granularin decreases phagocytic activity, and the encoding gene is upregulated in parasitized snails (160,161).…”
Section: Molluscan and Avian Host Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…Both molecules, produced in L. stagnalis by granular cells of connective tissue, are related to phagocytic activity of hemocytes. MDM enhances phagocytosis of hemocytes, and the expression of a corresponding gene for MDM is downregulated in L. stagnalis infected with T. szidati (159,161). In contrast, treatment of hemocytes with granularin decreases phagocytic activity, and the encoding gene is upregulated in parasitized snails (160,161).…”
Section: Molluscan and Avian Host Specificitymentioning
confidence: 99%
“…In the snail host, avian schistosomes also interfere with metabolism, such as causing abnormal body growth, and endocrine functions, such as causing a reduction of egg laying (161). In L. stagnalis, these processes are regulated by neuroendocrine cells in the central nervous system (CNS) (162,163).…”
Section: Molluscan and Avian Host Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible example of this is the effects of the schistosome parasite Tricholbilharzia ocellata on its snail host, Lymnaea stagnalis. The parasite secretes/excretes compounds that interfere with host immune function, allowing the survival of the parasite within the host (de Jong-Brink et al, 1997;de Jong-Brink et al, 2001). Infection also leads to a reduction in egg-laying in the snail, and the energy the host would have invested in reproduction is redirected to support parasitic growth (de Jong-Brink et al, 2001).…”
Section: Psychoneuroimmunological Mechanismsmentioning
confidence: 99%
“…Among these, neuropeptide Y or gonadotropin-releasing hormones act as a switch for nutritional status and reproduction, as demonstrated in vertebrates (e.g. Kalra and Kalra, 2004;Temple et al, 2003) and suggested in invertebrates (de Jong-Brink et al, 2001;Bigot et al, 2012Bigot et al, , 2014. Therefore, these neuropeptides represent a possible line of investigation into differences in reproductive strategy depending on modification in energy input from environmental and/or endogenous variations, whether natural or induced in the laboratory.…”
Section: Discussionmentioning
confidence: 99%